Celebrating Edward J. Latessa: Person, Builder, Scholar, and Traveler - Cullen, Francis T. (Victims & offenders, 2021)
Edward J. Latessa has had a multifaceted influence on the field of criminal justice over a remarkable career that has spanned more than four decades. He has been instrumental in building the School of Criminal Justice and a nationally recognized doctoral program at the University of Cincinnati, has contributed defining scholarly research, and has done more to shape correctional policy and practice than perhaps anyone else. The foundation of his impact, however, has been his unique personality and his commitment to improving the lives of others. This essay celebrates his career, focusing on Ed the person, the builder, the scholar, and the traveler.